2019
DOI: 10.1186/s12967-019-02150-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA methylation and copy number predict body composition in a young female population

Abstract: BackgroundSince both genomic and environmental factors are involved in obesity etiology, several studies about the influence of adiposity on both nuclear DNA and mitochondrial DNA methylation patterns have been carried out. Nevertheless, few evidences exploring the usage of buccal swab samples to study mitochondrial DNA epigenetics can be found in literature.MethodsIn this study, mitochondrial DNA from buccal swabs collected from a young Caucasian population (n = 69) have been used to examine potential correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…Indeed, EGCG-fed mice displayed higher body temperature and mtDNA content in BAT [244]. Of note, not only dietary antioxidants but other nutrients [245] or dietary regimen [246,247], as well as alteration of body composition [65], has shown association with mtDNA copy number, corroborating the hypothesis that diet and health status are strictly linked with the mtDNA function. Conversely, it has been recently demonstrated that alteration of mitochondrial DNA content can modulate antioxidant enzyme expressions and, consequentially, oxidative stress in the cell [248].…”
Section: Antioxidants and Mitochondria: From The General Function To supporting
confidence: 53%
See 2 more Smart Citations
“…Indeed, EGCG-fed mice displayed higher body temperature and mtDNA content in BAT [244]. Of note, not only dietary antioxidants but other nutrients [245] or dietary regimen [246,247], as well as alteration of body composition [65], has shown association with mtDNA copy number, corroborating the hypothesis that diet and health status are strictly linked with the mtDNA function. Conversely, it has been recently demonstrated that alteration of mitochondrial DNA content can modulate antioxidant enzyme expressions and, consequentially, oxidative stress in the cell [248].…”
Section: Antioxidants and Mitochondria: From The General Function To supporting
confidence: 53%
“…Since the efficiency and number of mitochondria can be manipulated by pharmacological and dietary treatments, it has been suggested that mitochondria may be a potential target for preventive medicine by tailoring personalized dietary approaches and supplementations [174]. Moreover, the emerging usage of mtDNA methylation and copy number as biomarkers [64,65,262,263] emphasizes the relevance of studies on mtDNA genomics and epigenomics, and reinforces the need for further investigations of this aspect, particularly with a focus on neurodegenerative disorders. Further research aimed to test the effects of dietary antioxidants on the mitochondrial genome are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MtDNA copy number was assessed as previously described [38] by a qPCR method using primers specific for mtDNA (mtpair21 fw-AATCCAAGCCTACGTTTTCACA; mtpair21 rv-AGTATGAGGAGCGTTATGGAGT) and normalizing for the amount of genomic DNA used in each reaction by using primers specific for gDNA (18s fw-GCAATTATTCCCCATGAACG; 18s-rv GGGACTTAATCAACGCAAGC). The qRT reaction was performed using Takara TB Green™ Premix Ex Taq™ II (Takara) and by using CFX-96 (Biorad).…”
Section: Mtdna Copy Number Evaluationmentioning
confidence: 99%
“…Epigenetic alterations (in particular DNA methylation) have been previously reported to play a role in CVD [16,17], gaining increasing interest in view of potential development of new therapeutic approaches [18,19], more efficient tools for early diagnosis [20] and personalized interventions [21]. While epigenetic regulation of nuclear DNA has been widely investigated, a relatively new field of research is represented by mitochondrial epigenetics [22][23][24][25]. Several studies identified variations of methylation levels in different areas of the mitochondrial genome, supporting the hypothesis that, similarly to nuclear epigenetics, mtDNA methylation could affect the expression of mitochondrial genes and mtDNA copy number as well [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%